2016
DOI: 10.1093/annonc/mdw188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the nanoparticle–drug conjugate CRLX101 in combination with bevacizumab in metastatic renal cell carcinoma: results of an investigator-initiated phase I–IIa clinical trial

Abstract: CRLX101 combined with bevacizumab is safe in mRCC. This combination fulfilled the protocol's predefined threshold for further examination with responses and prolonged PFS in a heavily pretreated population. A randomized phase II clinical trial in mRCC of this combination is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Prolonged stable disease with clear evidence of tumor shrinkage was observed in one patient with renal cell carcinoma (RCC) and in one patient with hepatocellular carcinoma (34). In the phase-I/IIa trial, CRLX101, a nanoparticle-drug conjugate containing camptothecin and polyethylene glycol that downregulated HIF-1α expression, was tested against metastatic RCC in combination with bevacizumab; five out of 22 patients (23%) achieved a partial response (35). The results of a phase-II trial of CRLX101 against recurrent ovarian, fallopian tube, or primary peritoneal cancer have also been reported (36).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged stable disease with clear evidence of tumor shrinkage was observed in one patient with renal cell carcinoma (RCC) and in one patient with hepatocellular carcinoma (34). In the phase-I/IIa trial, CRLX101, a nanoparticle-drug conjugate containing camptothecin and polyethylene glycol that downregulated HIF-1α expression, was tested against metastatic RCC in combination with bevacizumab; five out of 22 patients (23%) achieved a partial response (35). The results of a phase-II trial of CRLX101 against recurrent ovarian, fallopian tube, or primary peritoneal cancer have also been reported (36).…”
Section: Discussionmentioning
confidence: 99%
“…Another paclitaxel-based PEG-co-PLA nanomedicine is under phase III trial, Genexol-PM, has shown lower toxicity in the treatment of non-small cell lung cancer (NSCLC) and metastatic breast cancer [169]. CRLX-101, a cyclodextrin-conjugated camptothecin, is under clinical phase I/II trial for rectal cancer [170]. New targeted polymeric nanomaterials are also being introduced into clinical trials.…”
Section: Fda Approval and Clinical Trialsmentioning
confidence: 99%
“…For example, bevacizumab free drug has implications such as poor patient compliance due to the dosage frequency and drug resistance, however in the encapsulated form, there is sustained slow delivery of the drug and increased time between administrations, making the nanoparticle form more desirable [ 76 ]. Bevacizumab has also demonstrated promising synergistic response when combined with CRXL101, the nanoparticle form of camptothecin, in preclinical models [ 77 , 78 ]. CRLX101 in the nano form has a half-life of nearly 24 h, compared to a mere 2 h as a free drug, resulting in prolonged drug exposure and further emphasizing the significance of encapsulating drugs [ 78 ].…”
Section: Targeting Tumor Vasculaturementioning
confidence: 99%
“…Bevacizumab has also demonstrated promising synergistic response when combined with CRXL101, the nanoparticle form of camptothecin, in preclinical models [ 77 , 78 ]. CRLX101 in the nano form has a half-life of nearly 24 h, compared to a mere 2 h as a free drug, resulting in prolonged drug exposure and further emphasizing the significance of encapsulating drugs [ 78 ]. As a monotherapy treatment for platinum-resistant ovarian cancer in preclinical studies, CRLX101 is effective at maximum tolerated dosages, however frequent low-dose CRLX101 given in combination with bevacizumab yielded superior tumor reduction and minimal toxicity when compared to both drugs given as monotherapies [ 77 ].…”
Section: Targeting Tumor Vasculaturementioning
confidence: 99%